2011
DOI: 10.1111/j.1537-2995.2011.03403.x
|View full text |Cite
|
Sign up to set email alerts
|

Conversion to low transfusion‐related acute lung injury (TRALI)‐risk plasma significantly reduces TRALI

Abstract: The conversion to low-TRALI-risk plasma has reduced the incidence of TRALI reactions in plasma recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 16 publications
3
38
0
Order By: Relevance
“…Since then, explicit criteria applied under study conditions have varied. 34,35 Furthermore, while some authors reported TRALI rates, 33,36 others grouped TRALI and possible TRALI 37 (as we did).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Since then, explicit criteria applied under study conditions have varied. 34,35 Furthermore, while some authors reported TRALI rates, 33,36 others grouped TRALI and possible TRALI 37 (as we did).…”
Section: Discussionsupporting
confidence: 56%
“…Not only has TRALI recognition improved, but there have also been changes in blood management and donor procurement strategies that may have reduced the rate of TRALI. 10,11,37 Although our study did not demonstrate this hypothesized decline in incidence after TRALI mitigation strategies were introduced (as discussed in the next paragraph of this Discussion), a substantial and growing body of medical literature supports this effect. 11,37 Consequently, we believe that early data before the mid-2000s are unlikely to be representative of the current syndrome burden.…”
Section: Discussionmentioning
confidence: 55%
“…This technology has been used previously at our institution to develop screening algorithms for other critical care syndromes with great success. 1517 …”
Section: Methodsmentioning
confidence: 99%
“…German and Canadian hemovigilance systems also showed a decrease in the number of reported TRALI cases, 73,74 and a comparative cohort study from the Netherlands showed a 33% reduction of TRALI cases after implementation of a male‐only plasma strategy 75 . A retrospective study in three US hospitals showed a 0.0084% risk of TRALI from plasma transfusion (47,756 plasma units transfused) in the 16 months preceding implementation of low‐TRALI‐risk plasma versus 0% risk in the 16 months after implementation (52,230 plasma units transfused) 76 . Finally, in the only large active surveillance study of TRALI, TRALI incidence went from 1:4000 blood products transfused before mitigation to 1:12,000 after mitigation 38 .…”
Section: Tralimentioning
confidence: 99%